PRAKTIK JUAL RUGI (PREDATORY PRICING) PELAKU USAHA DALAM PERSPEKTIF PERSAINGAN USAHA - Riski Mada, I Dewa Gede; Sri Indrawati, A. A. (Kertha Semaya : Journal Ilmu Hukum, 2013)
Predatory pricing is the practice of selling goods or services at very low price, intending to drive competitors out of the relevant market, or create barriers to entry for potential new competitors. If competitors or potential competitors cannot sustain equal or lower prices without losing money,then the businesses will be eliminated from the competition or choose not to compete in relevant market.Therefore in this paper will describes the impact of the practice of predatory pricing in business competition, from short term to long term. And also will describes the legal consequences against businesses that engage in the practice predatory pricing.
Keywords: Predatory Pricing, Bussinesses, Business Competition